Introduction to the Special Issue: Interventions to Improve Children's Social and Emotional Functioning at School. (July 2016) - Collins, Tai A.; Hawkins, Renee O.; Nabors, Laura A.
Identification of evidence-based practices for promotion of social and emotional functioning of children at school is important for their academic and social development. This introduction reviews information from this special issue focusing on evidence-based research to improve the social and emotional functioning of children in their classrooms and schools. An emphasis on reduction of negative behaviors and promotion of positive, prosocial behaviors is presented in manuscripts for this special issue. The articles in this issue may be grouped in terms of the tiered system or School-Wide Positive Behavior Interventions and Supports Framework into articles at the Tier I, II, and III levels. Tier I interventions support positive behaviors and reduce problem behaviors for all children in a classroom or school, as a type of primary prevention. In terms of secondary prevention, Tier II interventions are selected interventions that address problem behaviors of students at risk for poor functioning, who do not respond to Tier I interventions. Finally, Tier III interventions are used for those students with behavioral and emotional issues who do not respond to Tier II interventions, and students in this group are indicated for intervention at a tertiary care level. In summary, this special issue presents evidence-based knowledge from research at all three intervention levels that aim to promote children's social and emotional development in the school setting.